Literature Review on the Effectiveness of Modern Dressing in the Wound Care Process on Diabetic Wound Healing - Alvod Edel Arkhad; Sufian Tuhfa; Zumara Dalina; Kamara Lalisa Loina; Elnara Manisa; Arfaana Bahisa Baheerah (Journal of Wound Research and Technology, 2024)
Background: Diabetes mellitus is a health problem due to insulin deficiency or insulin resistance that causes high blood glucose. A frequent complication is diabetic ulcer, which is a condition of partial or complete tissue deformity. If it does not get proper treatment, it is very risky to get an infection that leads to amputation.Diabetes Mellitus (DM) has become a prevalent disease, imposing a significant burden on public health due to its widespread occurrence and association with numerous disabilities and fatalities. Uncontrolled DM can lead to severe metabolic complications and long-term vascular issues, including microangiopathy and macroangiopathy. Additionally, individuals with DM are highly susceptible to foot infections, which can escalate into gangrene if not properly managed. Purpose: To determine the effectiveness of modern dressing in the wound care process on diabetic wound healing. Methods: Data collection used descriptive analysis and literature study. The databases used were PubMed, CINAHL, ProQuest and Web of Science. Journal inclusion criteria used PICO and article analysis was conducted by 6 authors. Findings: The evaluated article's findings elucidate the patient's degree of comfort and the more important healing process. It has been demonstrated that contemporary wound care applications make patients feel more at ease as their wounds heal, greatly aiding nurses in nursing care. Modern wound care is a practice that will evolve in response to advancements in nursing science; in this instance, it centers on how comfortable patients are while obtaining wound care-related medical treatments. Therefore, nurses must advance the knowledge behind the use of contemporary wound care to promote patient comfort and hasten the healing process. Conclusion: Modern wound care enhances patient comfort and accelerates healing, greatly supporting nursing practice. With evolving knowledge in nursing science, nurses need to master these methods to maximize patient comfort and recovery in wound care